Karaktersitik Pola Arus Laut di Perairan Selat Sunda Periode Tahun 2013 – 2023 - Latif Yuhana, Rofikoh; Guruh Pratomo, Danar; Khomsin, Khomsin (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2025)
This study examines the characteristics of ocean surface current patterns in the Sunda Strait using numerical model current data from Marine Copernicus during the period 2013 – 2023. The analysis was conducted to identify the direction and speed of currents in seasonal periods, namely the west season (December – January – February), transition season I (March – April – May), east season (June – July – August), and transition season II (September – October – November). Marine Copernicus model current data was verified against High Frequency (HF) Radar observation data using the statistical method of Pearson correlation coefficient (r) and Root Mean Square Error (RMSE), resulting in an r value of 0.77 and RMSE of 0.26 m/s, indicating a good level of accuracy. The results of the analysis show that in the west season, the dominant current heads northeast with an average speed of 0.5 – 1.0 m/s and a maximum of 1.5 – 2.0 m/s. In the first transitional season, the current flows to the northeast with an average speed of 0.75 – 1.25 m/s and a maximum of 1.5 – 2.0 m/s. In the east season, the dominant current flows to the southwest with an average speed of 1.25 – 1.75 m/s and a maximum of 1.5 – 2.0 m/s. In the second transitional season, the current flows irregularly towards the west and east, with an average speed of 1.0 – 1.5 m/s and a maximum of 1.5 – 2.0 m/s. These current patterns are influenced by monsoon winds, seabed topography, and coastal interactions, which impact navigation, fisheries, and marine ecosystems.